MODEL DISCOVERY LEARNING UNTUK MENINGKATKAN HASIL BELAJAR SISWA KELAS VII SMP - novi, Novi Hefriyanti; Juanda (Universitas Terbuka, 2023)
This research aims to increase student understanding, increase student creativity and activeness, and improve the quality of student learning outcomes regarding procedural texts through discovery learning models. The learning model applied by the teacher will affect student understanding. Low student understanding will affect student learning outcomes related to procedure text material. The source of this research data is information obtained from Class VII Junior High School students using random sampling of 20 students. The time of the study was conducted in November 2022. The data collected are quantitative data and qualitative data. Quantitative data is obtained from formative test results, and student learning outcomes. Data collection techniques use observation, documentation, and interviews. The results showed that there was an increase in student learning outcomes after learning with the discovery learning model, there were significant differences related to student learning outcomes in cycle I and cycle II. The result of the first cycle is that from the number of students as many as 20, there are 12 (60%) students who get scores above 70, and 8 (40%) students get scores below 70 with an average score of 72.05. In the second cycle, all 20 students scored above 70 with an average score of 76.35.